2018
DOI: 10.1007/s00005-018-0513-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in MiRNA-5196 Expression as a Potential Biomarker of Anti-TNF-α Therapy in Rheumatoid Arthritis and Ankylosing Spondylitis Patients

Abstract: In this study, we analysed the expression level of sera circulating miRNA-5196 in rheumatoid arthritis (RA) and ankylosing spondylitis (AS) patients before and after tumor necrosis factor (TNF)-α therapy as biomarkers predicting positive treatment outcome. We enrolled 10 RA patients, 13 AS patients, and 12 healthy individuals in the study. The expression of miRNA-5196 was measured by real-time polymerase chain reaction before and after anti-TNF-α therapy. Disease activity of RA patients was assessed using dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…Although lots of studies have shown that miRNA plays a crucial part in the progress of many kinds of cancer, evidences also showed that the abnormal expression of miRNAs in autoimmune diseases is not only an accidental event [ 10 , 19 21 ]. Studies from different research teams have shown that miRNAs were widely involved in the regulation of RA pathological and physiological processes, and play an important role in the proliferation, apoptosis, and inflammatory cascade reaction of different SF cells in RA, including miR-613, miR-126, miR-140-5p, miR-451, and so on [ 4 , 8 , 12 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although lots of studies have shown that miRNA plays a crucial part in the progress of many kinds of cancer, evidences also showed that the abnormal expression of miRNAs in autoimmune diseases is not only an accidental event [ 10 , 19 21 ]. Studies from different research teams have shown that miRNAs were widely involved in the regulation of RA pathological and physiological processes, and play an important role in the proliferation, apoptosis, and inflammatory cascade reaction of different SF cells in RA, including miR-613, miR-126, miR-140-5p, miR-451, and so on [ 4 , 8 , 12 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the hypothesis that anti-TNFα therapy might de-regulate miRNA expression, we first analyzed those studies that evaluated the miRNA expression in patients treated with anti-TNFα, and then compared the de-regulated miRNA with the PDAC findings reported in the DBDEMC2 database (see Table 2). Some studies in the literature report on the up- or down-regulation of miRNA following anti-TNFα therapy [94,95,96,97,98,99,100]. Notably, some miRNA (i.e., hsa-let-7d, hsa-miR-221, hsa-miR-224, hsa-miR-23a, and hsa-miR-197) were found to be up-regulated by anti-TNFα, and are reportedly associated with pancreatic cancer [91,101].…”
Section: Cytokines Released By Immune and Tumor Cells And Their Rmentioning
confidence: 99%
“…In contrast, Zhu et al reported that miRNA-23b inhibited IL-17-associated inflammation by targeting TGF- β binding protein 2 (TAB2) and TAB3 [18]. Our recent results demonstrated that sera circulating miRNA-5196 could be used as a biomarker predicting positive treatment outcome of TNF-α therapy in RA and ankylosing spondylitis patients, whereas single-nucleotide polymorphisms (SNPs) of miRNA-146a contribute to RA development [2,83]. Similarly, using genome-wide association study (GWAS) data, Wohlers et al reported that SNP rs968567 affected the expression of miR-1908-5p and contributed to RA predisposition [84].…”
Section: Epigenetic Predisposition For Ra Development With Particumentioning
confidence: 99%